2020
DOI: 10.3390/ijms21239241
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Fate of Legacy and Alternative Antimicrobials and Their Metabolites during Wastewater and Sludge Treatment

Abstract: Antimicrobial compounds are used in a broad range of personal care, consumer and healthcare products and are frequently encountered in modern life. The use of these compounds is being reexamined as their safety, effectiveness and necessity are increasingly being questioned by regulators and consumers alike. Wastewater often contains significant amounts of these chemicals, much of which ends up being released into the environment as existing wastewater and sludge treatment processes are simply not designed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 300 publications
0
14
0
Order By: Relevance
“…These properties typically enable TCC to have substantially higher antimicrobial concentrations in wastewater sludge as compared with TCS. TCS has high water solubility (10.0 mg/L) with a pKa of 7.9 and is prone to microbial degradation, preferentially being converted into its metabolites through biotic and abiotic processes and mechanisms within organisms and WWTPs as well as in the environment [ 20 , 56 , 57 ]. Whereas only a fraction of TCC in wastewater is removed through biologically mediated transformation and as a result of its molecular nature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These properties typically enable TCC to have substantially higher antimicrobial concentrations in wastewater sludge as compared with TCS. TCS has high water solubility (10.0 mg/L) with a pKa of 7.9 and is prone to microbial degradation, preferentially being converted into its metabolites through biotic and abiotic processes and mechanisms within organisms and WWTPs as well as in the environment [ 20 , 56 , 57 ]. Whereas only a fraction of TCC in wastewater is removed through biologically mediated transformation and as a result of its molecular nature.…”
Section: Resultsmentioning
confidence: 99%
“…Triclosan and triclocarban are relatively hydrophobic compounds with octanol/water coefficients (log Kow) of 4.8 and 4.9, respectively [ 13 ]. On the one hand, TCS has high water solubility (10.0 mg/L) with a pKa of 7.9, which enables it to be transformed into various other compounds through biotic and abiotic processes and mechanisms within organisms and WWTPs, as well as in the environment [ 20 ]. In this context, various aqueous environmental factors such as a change in water pH, temperature, photolytic process, and humidity, as well as living microorganisms (microalgae, fungi, microbacteria, and protists) are capable of degrading parent TCS into a more harmful daughter by-product such as chlorinated phenoxyphenols, chlorinated phenols, and trihalomethanes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Search for natural alternatives to synthetic food preservatives and disinfectants has been the subject of intensive research during the last decade. It has namely been stimulated by increasing concerns regarding their innocuity [e.g., nitrites ( EFSA Panel et al, 2017 ), sulfites ( EFSA Panel, 2016 ), polyhexamethylenebiguanide (PHMB), 5-chloro-2-(2,4-dichlorophenoxy)phenol (triclosan; Müller and Kramer, 2008 )] or their environmental impact [e.g., triclosan ( Abbott et al, 2020 )]. Regulatory changes [e.g., in the European Union (EU)] disinfectants are covered by the European Regulation concerning the marketing and use of biocidal products [ Regulation (EU) no 528/2012, 2012 ] and increasing demand of consumers for organic foods (in which only a limited number of food preservatives are authorized) or for «clean label» food products (without or with a limited number of food additives such as food preservatives) are important drivers of this trend.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the occurrence of TCC and its intermediates in wastewater effluent, surface water, biosolid, sediment and soil [ 31 , 32 ]. TCC is ranked, in fact, in the top 10 Contaminant of Emerging Concern (CEC) occurrence [ 31 , 33 , 34 ]. Once conveyed to wastewater treatment plants, PPCPs can remain unchanged or undergo a partial or complete transformation during wastewater treatment processes before being discharged into the environment via effluent and biosolids for land application.…”
Section: Introductionmentioning
confidence: 99%